A COMPARATIVE ANALYSIS OF SOME SHOPPING CENTERS IN METROPOL CITIES OF TURKIYE USING IPA AND IPCA METHODS - ÖZTÜRK, Sevgi; IŞINKARALAR, Öznur; YILMAZ, Dilara; KESİMOĞLU, Feyza (Dokuz Eylul University, 2023)
With the influence of globalization and modernism, habits have begun to change in many areas. Especially in recent years, as a result of economic and social events, the urban lifestyle has also changed. As a result of the change, people have started to prefer multifunctional shopping centers where all kinds of products, in addition to their basic needs, are available together and where they can have more rest opportunities. Areas with this function, which are also considered urban attraction points, are increasing their share in the service sector day by day. There is a highly competitive environment among shopping malls that have a significant customer potential. Understanding the competitive position of these areas is vital for decision-makers. This study, conducted in Ankara and Istanbul samples, aims to analyze to what extent the physical features of shopping malls meet the preferences and expectations of users. These properties were evaluated using IPA and IPCA methods. In this context, the study presents a comparative analysis of Ankara, which was selected as the focal location, and Istanbul, which was selected as the rival location. As a result of the analysis, the criteria that Ankara and Istanbul have higher performance than each other and the features that should be prioritized in performance improvement studies to increase their competitiveness were determined. It has been concluded that shopping malls in Ankara are in a position to compete with Istanbul.
Keywords: 11. Sustainability; 1. No poverty